Santo Tomás de Aquino y el Maestro Eckhart. Alcances en torno al ejemplo noético del muro en el De unitate intellectus contra averroistas - Paredes Díaz, Sandro; Albornoz Olivares, Mauricio (Pontificia Universidad Católica del Perú, 2024)
The relationship between Thomas Aquinas and Meister Eckhart is –especially with regards to noetics– a complex matter. This paper explores the possibility of identifying coincidences and differences in their approaches starting from the noetic example of the wall used by Thomas in De unitate intellectus, which Eckhart also mentions in some of his works. I present an analysis of the example of the wall and of its use by Eckhart in a group of his sermons and treatises. As a conclusion, I claim that Eckhart, though acquainted with Thomas’ position, develops a perspective that goes beyond the Thomist framework.

La relación entre Santo Tomás de Aquino y el Maestro Eckhart es un tema complejo, especialmente en lo referido a la noética. Nuestro trabajo explora la posibilidad de establecer conexiones y diferencias a partir del ejemplo noético del muro usado por el Aquinate en De unitate intellectus, y al cual Eckhart hace referencia en algunas de sus obras. Se ofrece un análisis del ejemplo del muro y su uso por parte de Eckhart en algunos de sus sermones y tratados. A partir de ahí, se concluye que la perspectiva de Eckhart, si bien conoce la posición del Aquinate, supera los esquemas tomistas.
Thomas Aquinas and Meister Eckhart. Observations concerning the Noetic Example of the Wall in De unitate intellectus
Keywords: Thomas Aquinas; Eckhart; Noetics; Intellect; Averroism; Tomás de Aquino; Eckhart; Noética; Intelecto; Averroísmo; https://purl.org/pe-repo/ocde/ford#6.03.01